2009
DOI: 10.1093/nar/gkp890
|View full text |Cite
|
Sign up to set email alerts
|

The 5'-untranslated region of the mouse mammary tumor virus mRNA exhibits cap-independent translation initiation

Abstract: In this study, we demonstrate the identification of an internal ribosome entry site (IRES) within the 5′-untranslated region (5′-UTR) of the mouse mammary tumor virus (MMTV). The 5′-UTR of the full-length mRNA derived from the infectious, complete MMTV genome was cloned into a dual luciferase reporter construct containing an upstream Renilla luciferase gene (RLuc) and a downstream firefly luciferase gene (FLuc). In rabbit reticulocyte lysate, the MMTV 5′-UTR was capable of driving translation of the second cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(99 citation statements)
references
References 67 publications
9
90
0
Order By: Relevance
“…RNA concentrations were determined spectrophotometri- (31). The RNA was translated in nucleasetreated RRL as previously described (32). The L-protease-RRL was diluted 1:5 or 1:10 in nuclease-free water (IDT) and added (to a final concentration of 3 and 6% [vol/vol]) to the fresh nuclease-treated 35% (vol/vol) RRL and preincubated for 15 min at 30°C, prior to the addition of the bicistronic mRNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA concentrations were determined spectrophotometri- (31). The RNA was translated in nucleasetreated RRL as previously described (32). The L-protease-RRL was diluted 1:5 or 1:10 in nuclease-free water (IDT) and added (to a final concentration of 3 and 6% [vol/vol]) to the fresh nuclease-treated 35% (vol/vol) RRL and preincubated for 15 min at 30°C, prior to the addition of the bicistronic mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Oocytes were isolated from Xenopus laevis ovarian fragments by manual dissection as previously described (32). Oocytes were incubated at 15°C for 24 h in standard Barth's solution supplemented with 10 IU of penicillin-streptomycin/liter and 2 mM pyruvate (32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012). Although the presence of an IRES element is a common feature of all picornavirus RNAs, some differences affecting the organization of the 5 UTR, described below, are specific of each genus.…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%